Analysis of the Bubble Assets Phenomenon in Yogyakarta - Elisa Aura Maharani; Riani, Lilia Pasca (Universitas Nusantara PGRI Kediri, 2025)
Research aim : Study This aiming For analyze the bubble assets phenomenon in Yogyakarta, especially driving factors​ inflation price property as well as impact socio-economic to public local . Design/Method/ Approach : research This use approach descriptive qualitative with method studies literature , statistical data analysis , and interview deep with stakeholders interest main , including resident local , investors, and makers policy . Research Finding : Research results show that surge price properties in Yogyakarta especially driven by increasing interest investment , behavior speculative , as well as weakness regulation market control . Phenomenon This cause problem accessibility housing area for public local as well as potential risk crisis economy if the bubble bursts . Theoretical contribution/ Originality : Study This contribute to understanding about bubble assets in the economy urban development​ growing , especially in cities with growth rapid in the sector tourism and urbanization . This study highlight role investment speculative and loopholes policy in to worsen property market imbalance . Practitionel /Policy implications : Findings study This show the need more spatial planning policies​ strict , regulation tax For reduce purchase speculative , as well as housing programs affordable use ensure development inclusive economy . Intervention​ government area is very much needed For stabilize the market and protect public prone to from impact negative phenomenon This . Research limitations: This study own limitations in approach qualitative as well as property market data availability in real-time. Research furthermore can combining quantitative models as well as studies more cases​ wide For increase accuracy prediction .